2023
DOI: 10.1111/aos.15683
|View full text |Cite
|
Sign up to set email alerts
|

Visual function in adults born preterm with very low birth weight—A two‐country birth cohort study

Abstract: PurposeThe purpose of the study was to investigate visual function and vision‐related general health in adults that were born preterm with very low birth weight (VLBW: birth weight < 1500 g) in their 30s–40s.MethodsWe recruited 137 adults born preterm with VLBW and 158 term‐born controls aged 31–43 years from two birth cohorts: the Helsinki Study of Very Low Birth Weight Adults (Finland) and the NTNU Low Birth Weight in a Lifetime Perspective study (Norway). We used neonatal data and measured refraction, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, two review articles have shown that adolescents and adults born VP/VLBW have more motor impairments compared with term-born controls [ 6 , 41 ]. Secondly and relatedly, motor difficulties could also be associated with visual problems found in adolescence [ 42 ] and adulthood [ 43 , 44 ]. These conditions may affect the ability to perform everyday life functional activities including a physically active lifestyle [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, two review articles have shown that adolescents and adults born VP/VLBW have more motor impairments compared with term-born controls [ 6 , 41 ]. Secondly and relatedly, motor difficulties could also be associated with visual problems found in adolescence [ 42 ] and adulthood [ 43 , 44 ]. These conditions may affect the ability to perform everyday life functional activities including a physically active lifestyle [ 9 ].…”
Section: Discussionmentioning
confidence: 99%